Tratamiento en intoxicación por Paraquat y sus repercusiones a corto y largo plazo. - Figueroa Yépez, Jordy Baldomero (2025)
This study provides a comprehensive understanding of paraquat poisoning by examining its mechanisms of action, the body’s response to treatment, and its impact on various organs. A review of recent literature shows that paraquat induces severe oxidative damage, particularly affecting vital organs such as the lungs, liver, and kidneys. Among these, lung damage is the most critical, as it often results in irreversible pulmonary fibrosis, significantly impairing respiratory function and representing a major cause of mortality in affected individuals. After ingestion, paraquat is rapidly absorbed and predominantly accumulates in the lungs, where it triggers intense oxidative stress. This process leads to the generation of free radicals, which damage cellular components and disrupt mitochondrial function, ultimately causing cell death through apoptosis or necrosis. Current treatment approaches focus primarily on life support measures, including extracorporeal elimination techniques and the administration of antioxidants. However, their effectiveness varies depending on factors such as the timing of intervention and the patient’s renal function. Additionally, research has identified long-term consequences of paraquat exposure, including an elevated risk of developing neurodegenerative diseases. These findings underscore the urgent need to enhance preventive strategies, increase awareness about the safe handling of paraquat, and support further research aimed at developing more effective treatments to reduce the high mortality rate associated with this form of poisoning.